Implementation of an Integrated Curriculum in Improving Arabic Speaking Skills - Najwa, Nafisatun; Maulana, Asep; Maskud, Maskud (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
The aim of this research was to determine the implementation of an integrated curriculum in language learning, especially Mahararah kalam. As material for improving the curriculum, researchers also discussed learning problems. This research was descriptive qualitative research at Foreign Language Development Institute (LPBA) at Al Yasini Islamic Boarding School, Pasuruan. Data collection techniques were carried out through interview techniques and documentation with related parties. Meanwhile, the data analysis technique used reduction, selection, data collection and data display techniques. The results showed that the LPBA carries an integrated curriculum innovation model. This can be seen from the learning practices carried out. So, at the the Arabic language development institute at Al Yasini and in the language boarding schools, students are accustomed to communicating using Arabic implementing the vocabulary in the teaching materials that have been taught. In addition, the components contained in this learning are also in accordance with the integration of the curriculum used by combining the Arabic language that has been studied with several existing lessons.